Clinical treatment of cluster headache with the serotonergic indoleamine psychedelics psilocybin and LSD and with ketamine: A case series - Jonathan Leighton; Carmen Lau; Aisha Savdo; Livia Granata (Cephalalgia Reports)
Background Cluster headache is an excruciating condition for which standard treatments are usually insufficient. Evidence has accumulated that serotonergic psychedelic indoleamines including psilocybin and LSD can be effective in preventing attacks. Methods In this case series, nine patients with episodic and chronic cluster headache that didn’t respond to conventional treatments were treated at a clinic with psilocybin or LSD, under compassionate use provisions, and in most cases separately with ketamine. Results All patients responded positively to at least one of the treatments, and eight of nine responded positively to the treatment with the psychedelic indoleamines, in several cases with extended periods free of attacks. Conclusion These clinical data, though of an exploratory nature, add to the existing pool of evidence for the usefulness of these substances for treating cluster headache, and further support the lowering of legal and regulatory barriers to medical access to the psychedelic indoleamines.